2021
DOI: 10.3389/fimmu.2021.621503
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenic Missense Variant in NFKB1 Causes Common Variable Immunodeficiency Due to Detrimental Protein Damage

Abstract: In common variable immunodeficiency (CVID), heterozygous damaging NFKB1 variants represent the most frequent monogenic cause. NFKB1 encodes the precursor p105, which undergoes proteasomal processing to generate the mature NF-κB transcription factor subunit p50. The majority of NFKB1 sequence changes comprises missense variants of uncertain significance (VUS), each requiring functional evaluation to assess causality, particularly in families with multiple affected members presenting with different phenotypes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
(82 reference statements)
3
24
0
Order By: Relevance
“…The latter patient additionally carried the known p.Cys104Arg mutation in TNFRSF13B. Although functional in vitro testing, as previously described (23), indicated that none of these four variants cause a detrimental protein loss, we could not exclude a hypomorphic reduction of protein function (data not shown). Using reporter assays, a recent study demonstrated a loss-of-function for p.Arg57Cys, whereas a functional defect associated with p.Tyr90Ser, p.Arg214Gln, and p.Met216Val, remained obscure (63).…”
Section: Mutations In Nfkb1 and Nfkb2mentioning
confidence: 63%
See 1 more Smart Citation
“…The latter patient additionally carried the known p.Cys104Arg mutation in TNFRSF13B. Although functional in vitro testing, as previously described (23), indicated that none of these four variants cause a detrimental protein loss, we could not exclude a hypomorphic reduction of protein function (data not shown). Using reporter assays, a recent study demonstrated a loss-of-function for p.Arg57Cys, whereas a functional defect associated with p.Tyr90Ser, p.Arg214Gln, and p.Met216Val, remained obscure (63).…”
Section: Mutations In Nfkb1 and Nfkb2mentioning
confidence: 63%
“…Levels of Adenosine deaminase 1 or 2 (ADA and ADA2) were evaluated by measuring the specific enzyme activity in Michael S. Hershfield's lab at Duke University School of Medicine (USA) and at the Advanced Diagnostic Unit, University of Freiburg (Germany), respectively. NFKB1 variants were analyzed as described previously (23).…”
Section: Variant Evaluation By Functional Assaysmentioning
confidence: 99%
“…Patients with this defect manifest hypogammaglobulinemia due to decreased switched memory B cells, and diminished lymphocyte proliferation after stimulation with B cell mitogens. It seems that the patients usually have a normal response to T-dependent and T-independent antigens ( 86 ).…”
Section: Nfkb1 Deficiencymentioning
confidence: 99%
“…In addition, frameshift variants in the central part of p105, predict immediate expression of p50-like proteins, which by-pass the precursor stage ( 19 , 20 ), as well as the sporadically occurring C-terminal truncations ( 21 , 22 ), are also considered to have a pathogenic effect, although the disease-causing mechanisms are still unknown for both entities. The pathogenic significance of most (51/54 and 31/33) of the identified NFKB1 missense alterations, however, remained uncertain ( 7 , 10 ) unless experimental confirmation of their causality became available ( 18 , 23 ). Amino acid changes localizing to the N-terminal half (aa 1-433) affect both the p105 precursor and the p50 subunit.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, we used a standard cell culture model, based on transient transfection of HEK293T cells with EGFP-fused p105 and p50 constructs, enabling functional assessments of NFKB1 missense variants ( 23 ). Subsequent analyses, including expression and subcellular localization of the overexpressed proteins as well as p50-dependent DNA-binding and RelA-mediated reporter gene activation, confirmed a detrimental protein loss caused by a single amino acid change (p.Tyr350Cys) in a CVID family with p105/p50 haploinsufficiency.…”
Section: Introductionmentioning
confidence: 99%